Learning management system utilization and perceived training benefits among vocational teachers - Kurniawati Kurniawati; Tuti Suartini (Jurnal Pendidikan Vokasi, 2025)
The use of Learning Management Systems (LMS) in teacher training is now an important strategy for improving professional competence in the digital era, especially in vocational education in business and tourism. However, so far, little research has specifically examined the relationship between LMS use and the benefits teachers experience after participating in training. Given these conditions, this study was conducted to analyze the relationship between LMS utilization and training benefits from the perspective of upskilling and reskilling program participants. The study used a quantitative approach with a questionnaire instrument distributed to 108 teachers who had participated in the upskilling and reskilling program. The data were processed using descriptive statistics and Spearman's Rho correlation test due to their non-normal distribution. The analysis results showed a strong positive relationship between LMS utilization and training benefits (ρ = 0.771; p < 0.001). This means that the more effectively the LMS is used during training, the greater the benefits for teachers, especially in terms of ease of access to materials, increased interaction, and strengthened professional competencies. Thus, the LMS not only serves as a platform for delivering materials but also becomes a medium for reflective learning and supports the professional development of vocational teachers. The results of this study provide practical contributions for training institutions and policymakers to strengthen the implementation of LMS in teacher development, while also opening space for further research on its long-term impact on the quality of learning in vocational high schools.